(untitled) (Vietnam Journal of Community Medicine, 2024)
In recent years, the Mekong delta has been facing challenges from climate change, water shortages, saltwater intrusion as well as other increasingly serious extreme weather phenomena. These are factors considered to be at risk of causing or worsening skin diseases. Objective: Assess the current status of common skin diseases in the community, epidemiological characteristics and some factors related to skin diseases in Nam Du archipelago. Research methods: Performed cross-sectional description on 233 patients with skin diseases in Nam Du archipelago, Kien Hai district, Kien Giang province. Results: At least 28 types of skin diseases were found in 233 patients in Nam Du archipelago. Contact dermatitis is the skin disease with the highest proportion with 29.3%, atopic dermatitis 18.8%, and skin fungus 7.4%. The number of common skin diseases is 1 disease/person (90.1%). Up to 87.1% of patients with skin diseases do not receive treatment or self-treat, and the rate of patients with concurrent diseases is 31.8%. The two most common treatment difficulties for patients on the island are travel and time. Some factors were linearly correlated with skin diseases such as exposure to adverse factors in the living and working environment, use of bath products, water use and some eating habits patient’s drink. Conclusion: The study results are the basis for making recommendations and conducting further research on skin diseases in rural areas in the Nam Du islands.